Carbon nano composite fiber, preparation method thereof and application of carbon nano composite fiber in preparation of flexible woven fabric capacitor
By preparing carbon nanocomposite fibers, combining the structural advantages of multi-walled carbon nanotubes and ordered porous carbon, the flexibility and micro-power requirements of energy storage devices in microelectronic systems are solved, and flexible wovenable capacitors with high specific capacitance and stability are achieved.
Patent Information
- Application Number
- CN202411609347.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to provide an energy storage device that meets the needs of micro-volume, flexible material design, reliable electrochemical cycle characteristics, and micro-power design, especially in the field of micro-electronic systems.
By preparing a carbon nanocomposite fiber, using multi-walled carbon nanotubes as the skeleton, and integrating ordered porous carbon on it to form a laminar flow structure MWCNT/OMC composite material is used to prepare flexible woven fabric capacitors.
Flexible woven fabric capacitors that achieve high specific capacitance and long life stability are suitable for portable and wearable electronic devices, and the capacitance wires are lightweight and can be integrated into a variety of textile structures.
Smart Images

Figure CN119685973A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nuclear battery energy storage, and specifically relates to a carbon nanocomposite fiber and a preparation method thereof, and an application thereof in the preparation of a flexible weavable capacitor. Background Art
[0002] With the increasing use of fossil fuels and the environmental pollution they bring, there is an urgent need for more efficient, cleaner and renewable energy. Common sustainable energy sources (wind, solar, tidal and geothermal) have seasonal characteristics, so they require special equipment for energy conversion and storage to improve the efficiency and sustainability of energy systems. For the application field of nuclear decay energy, that is, the field of nuclear batteries, the demand for micro-power energy storage devices is particularly obvious. In many application fields, the most effective and practical energy conversion and storage devices are batteries, supercapacitors, solar cells, and fuel cells. Among them, capacitors as a new type of energy storage device have a strong appeal to researchers, mainly due to their high power density, superior fast charge-discharge capability (within a few seconds) and ultra-long cycle life (>100,000 cycles). These advantages are based on the electric double layer capacitor (Edlc) effect and the charge insertion and extraction (pseudocapacitance effect) on the surface of carbon electrode materials (such as activated carbon, mesoporous carbon, carbon nanofibers, graphene).
[0003] In order to meet the development of small and faster electronic devices in modern optoelectronics and electronics, it is crucial to find energy storage devices that can match electrochemical capacitors, etc. Traditional planar structures can no longer meet the driving requirements. In the field of microelectronic systems (MEMS), volume has become a key limiting factor in device performance. With the prospect of MEMS development towards miniaturization, centralized power density, and highly integrated devices, the demand for miniature, flexible, and micro-power energy storage devices is growing. However, in the current application field, there is a lack of energy storage devices that meet the requirements of small size, flexible material design, reliable electrochemical cycle characteristics, and micro-power design.
[0004] Carbon nanotubes and ordered mesoporous carbon. Carbon nanomaterials have been widely studied and applied in the energy storage process of electrode materials due to their outstanding chemical and physical properties. Among them, carbon nanotubes (CNT) and ordered mesoporous carbon (OMC) are the two most popular systems. CNT electrodes are usually prepared by a simple solution process. The unique one-dimensional high conductivity structure is conducive to the separation and transport of charges. However, the morphology of currently used carbon nanotubes is random and dispersed. The charges must cross a large number of boundaries during the migration process. When passing through the boundary resistance, the charges will consume a lot of energy and reduce the migration efficiency. The macroscopic effect is that the charging and discharging efficiency is greatly reduced. OMC itself has the limitations of orderly distribution and low conductivity.
[0005] Carbon nanomaterials have been widely studied and applied in the energy storage process of electrode materials due to their outstanding chemical and physical properties. Among them, carbon nanotubes (CNTs) and ordered mesoporous carbon (OMC) are the two most popular systems. CNT electrodes are usually prepared by a simple solution process. The unique one-dimensional high conductivity structure is conducive to the separation and transport of charges. However, the morphology of currently used carbon nanotubes is random and dispersed. The charges must cross a large number of boundaries during the migration process. When passing through the boundary resistance, the charges will consume a lot of energy and reduce the migration efficiency. The macroscopic effect is that the charging and discharging efficiency is greatly reduced. OMC itself has the limitation of orderly distribution and the disadvantage of low conductivity. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing carbon nanocomposite fibers.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0010] The carbon precursor furanol is dissolved in anhydrous ethanol to form a carbon precursor solution;
[0011] The carbon precursor solution is added dropwise to the SBA-15 template, and polymerized at 50-70°C and 140-160°C for 4-6 hours by magnetic stirring, and the polymerized product is heated by vacuum heating and tubular furnace heating to obtain a heated product;
[0012] The heated product was then treated with a 40% HF solution, rinsed with fibers, and washed with deionized water to obtain an ordered porous carbon OMC.
[0013] Fe / Al 2 O 3 deposited on a silicon wafer by electron beam evaporation as a catalyst, ethylene as a carbon precursor, H 2 With Ar as the carrier gas, the multi-walled carbon nanotube array MWCNT is continuously grown and deposited;
[0014] Ordered porous carbon is dispersed in N, N-dimethylformamide to obtain an OMC solution, three layers of MWCNT sheets are stacked to form a laminar structure, the OMC solution is added, and rolling is performed to form a MWCNT / OMC composite material, namely, carbon nanocomposite fibers.
[0015] As a preferred embodiment of the method for preparing the carbon nanocomposite fibers of the present invention, the mass volume ratio of furanol to anhydrous ethanol in the carbon precursor solution is 1-3 g:3 ml.
[0016] As a preferred embodiment of the method for preparing the carbon nanocomposite fibers of the present invention, the vacuum heating temperature of the polymerization product is 130-170°C, the heating time is 1-3 hours, and the tubular furnace heating temperature is 800-1000°C, the heating time is 2-4 hours.
[0017] As a preferred embodiment of the method for preparing the carbon nanocomposite fiber of the present invention, wherein: the Fe / Al 2 O 3 The thicknesses deposited on the silicon wafer are 1-2nm and 4-6nm respectively.
[0018] As a preferred embodiment of the method for preparing the carbon nanocomposite fiber of the present invention, the carrying gas H 2 The flow rate of is 25~35sccm, and the flow rate of Ar is 350~450sccm.
[0019] As a preferred solution of the method for preparing the carbon nanocomposite fibers of the present invention, the concentration of the OMC solution is 0.1-1 mg / ml.
[0020] Another object of the present invention is to provide a carbon nanocomposite fiber, wherein the carbon nanocomposite fiber has multi-walled carbon nanotubes as a skeleton and is highly arranged along the axial direction, and the ordered porous carbon is interconnected between the aligned multi-walled carbon nanotubes.
[0021] Another object of the present invention is to provide an application of carbon nanocomposite fibers in the preparation of flexible weavable capacitors.
[0022] Another object of the present invention is to provide a flexible weavable capacitor.
[0023] As a preferred embodiment of the method for preparing the flexible woven capacitor of the present invention, polyvinyl alcohol is added to deionized water, stirred at room temperature for 5 to 7 hours, and then heated at 80 to 100° C. under magnetic stirring conditions to obtain a mixed solution, and H 3 PO 4 Added into the mixed solution to generate a gel electrolyte, wherein the polyvinyl alcohol and H 3 PO 4The mass ratio of polyvinyl alcohol to deionized water is 1g:8-12ml;
[0024] The surfaces of every two carbon nanocomposite fiber MWCNT / OMC composite materials are coated with gel electrolyte and twisted together to form a filamentary electric double layer capacitor EDLC, which is a flexible weavable capacitor based on carbon nanocomposite fibers.
[0025] Beneficial effects of the present invention:
[0026] The present invention develops a flexible, braidable EDLC wire by twisting two arranged MWCNT / OMC composite optical fibers as electrodes. Since OMC is integrated into the axially arranged MWCNT skeleton, thus combining the structural and performance advantages of the two components in the composite optical fiber electrode, the EDLC wire has a high specific capacitance and long life stability. Compared with traditional planar structures, the capacitive wire is also light and can be integrated into various textile structures, especially suitable for portable and wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0028] Figure 1 This is a schematic diagram of the structure of the carbon nanocomposite fiber synthesized in Example 1 of the present invention.
[0029] Figure 2 This is a schematic diagram of the structure of the flexible weavable capacitor synthesized in Example 2 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0033] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.
[0034] Example 1
[0035] The present invention provides a method for preparing carbon nanocomposite fibers (MWCNT / OMC), specifically:
[0036] 1) 4 g of poly(ethylene glycol)-b-poly(propylene glycol)-b-poly(ethylene glycol) was added to 130 mL of 1.6 M hydrochloric acid, and then 10.7 g of tetraethylchlorosilicate was added, and the mixture was reacted at 40° C. for 2 h to obtain a white solution;
[0037] The white solution was transferred to an autoclave and aged at 100°C for 24 hours. After the aging, it was washed with deionized water, dried at 80°C for 12 hours, and then calcined at 550°C for 5 hours to generate an SBA-15 template.
[0038] 2) 2 g of furanol as a carbon precursor was dissolved in 3 mL of anhydrous ethanol to obtain a carbon precursor solution, which was then dropped into an SBA-15 template at room temperature and magnetically stirred for 1 h. The mixture was polymerized in air at 60°C and 150°C for 5 h, respectively. The product was heated in a vacuum at 150°C to remove unreacted furfuryl alcohol. After vacuum heating, the product was transferred to a tubular furnace and heated at 900°C for 3 h. The heated product was treated with a 40% HF solution for 1 h to remove silica, followed by fiber rinsing and deionized water washing to obtain ordered porous carbon OMC.
[0039] 3) In a quartz tube furnace with a diameter of 2 inches, a multi-walled carbon nanotube (MWCNT) array was synthesized by chemical vapor deposition. Specifically, Fe (1.5 nm) / Al 2 O 3 (5 nm) deposited on a silicon wafer by electron beam evaporation, ethylene as a catalyst, H 2 (30 sccm) and Ar (400 sccm) were used as the carrying gas and the growth was continued at 740 °C for 10 min to obtain the MWCNT array.
[0040] 4) OMC was dispersed in N,N-dimethylformamide to obtain a solution with a concentration of 0.5 mg / mL. A MWCNT sheet with a width of 1.5 cm was taken out from the MWCNT array. Three layers of MWCNT sheets were stacked to form a laminar structure. OMC solution was added and rolled to form a MWCNT / OMC composite material. The structural schematic diagram is shown in FIG. Figure 1 As shown, the backbone MWCNTs are highly aligned along the axial direction, while the OMCs are interconnected between the aligned MWCNTs.
[0041] Example 2
[0042] This embodiment provides a method for preparing a flexible weavable capacitor based on carbon nanocomposite fibers (MWCNT / OMC), specifically:
[0043] 1) Polyvinyl alcohol (0.67 g) was added to 6.04 g of deionized water, stirred at room temperature for 6 hours and then heated at 90 °C under magnetic stirring to obtain a mixed solution. 31 PO 4 (0.67 g) was added to the mixed solution to form a gel electrolyte;
[0044] 2) The surfaces of two MWCNT / OMC composite materials prepared in Example 1 are coated with the gel electrolyte obtained in step 5) and then twisted together to form a filamentary electric double layer capacitor EDLC, that is, a flexible weavable capacitor based on carbon nanocomposite fibers.
[0045] Example 3
[0046] The difference between this embodiment and embodiment 1 is that the concentration of the OMC solution in step 4) is adjusted to 0.1 mg / mL, and the remaining steps and processes are all referred to embodiment 1 to obtain the MWCNT / OMC composite material of this embodiment;
[0047] Further referring to the method of Example 2, the MWCNT / OMC composite material of this example is used to prepare a flexible weavable capacitor to obtain the filamentary electric double layer capacitor EDLC of this example.
[0048] Example 4
[0049] The difference between this embodiment and embodiment 1 is that the concentration of the OMC solution in step 4) is adjusted to 0.25 mg / mL, and the remaining steps and processes are all referred to embodiment 1 to obtain the MWCNT / OMC composite material of this embodiment;
[0050] Further referring to the method of Example 2, the MWCNT / OMC composite material of this example is used to prepare a flexible weavable capacitor to obtain the filamentary electric double layer capacitor EDLC of this example.
[0051] Example 5
[0052] The difference between this embodiment and embodiment 1 is that the concentration of the OMC solution in step 4) is adjusted to 0.75 mg / mL, and the remaining steps and processes are all referred to embodiment 1 to obtain the MWCNT / OMC composite material of this embodiment;
[0053] Further referring to the method of Example 2, the MWCNT / OMC composite material of this example is used to prepare a flexible weavable capacitor to obtain the filamentary electric double layer capacitor EDLC of this example.
[0054] Example 6
[0055] The difference between this embodiment and embodiment 1 is that the concentration of the OMC solution in step 4) is adjusted to 1 mg / mL, and the remaining steps and processes are all referred to embodiment 1 to obtain the MWCNT / OMC composite material of this embodiment;
[0056] Further referring to the method of Example 2, the MWCNT / OMC composite material of this example is used to prepare a flexible weavable capacitor to obtain the filamentary electric double layer capacitor EDLC of this example.
[0057] The energy densities of the filamentary electric double layer capacitors EDLC prepared in Examples 2 to 6 are compared, and the results are shown in Table 1.
[0058] Table 1
[0059]
[0060] The energy density of the EDLC in the present invention is determined by the conductivity of the electrode and the diffusion kinetics of ions in the electrolyte, which can be increased by the arrangement of MWCNTs. For OMCs with relatively small mesopores (2-6nm) and long ion diffusion distances (1-2μm), lower conductivity and diffusion efficiency are produced.
[0061] In summary, the present invention has developed a flexible, braidable EDLC wire by twisting two aligned MWCNT / OMC composite fibers as electrodes. Since the OMC is integrated into the axially aligned MWCNT skeleton, thereby combining the structural and performance advantages of the two components in the composite fiber electrode, the EDLC wire has a high specific capacitance and long life stability. Compared with traditional planar structures, the capacitive wire is also light and can be integrated into various textile structures, especially suitable for portable and wearable electronic devices.
[0062] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing carbon nanocomposite fibers, characterized in that: include, The carbon precursor furanol is dissolved in anhydrous ethanol to form a carbon precursor solution; The carbon precursor solution is added dropwise to the SBA-15 template, and polymerized at 50-70°C and 140-160°C for 4-6 hours by magnetic stirring, and the polymerized product is heated by vacuum heating and tubular furnace heating to obtain a heated product; The heated product was then treated with a 40% HF solution, rinsed with fibers, and washed with deionized water to obtain an ordered porous carbon OMC. Fe / Al2O3 was deposited on a silicon wafer as a catalyst by electron beam evaporation, ethylene was used as a carbon precursor, H2 and Ar were used as carrier gases, and multi-walled carbon nanotube arrays MWCNT were obtained by continuous growth and deposition; Ordered porous carbon is dispersed in N, N-dimethylformamide to obtain an OMC solution, three layers of MWCNT sheets are stacked to form a laminar structure, the OMC solution is added, and rolling is performed to form a MWCNT / OMC composite material, namely, carbon nanocomposite fibers.
2. The method for preparing carbon nanocomposite fibers according to claim 1, wherein: The mass volume ratio of furanol to anhydrous ethanol in the carbon precursor solution is 1-3 g:3 ml.
3. The method for preparing carbon nanocomposite fibers according to claim 1, wherein: The vacuum heating temperature of the polymer product is 130-170° C., and the heating time is 1-3 hours. The tubular furnace heating temperature is 800-1000° C., and the heating time is 2-4 hours.
4. The method for preparing carbon nanocomposite fibers according to claim 1, wherein: The thickness of the Fe / Al2O3 deposited on the silicon wafer is 1-2nm and 4-6nm respectively.
5. The method for preparing carbon nanocomposite fibers according to claim 1, wherein: The flow rate of the carrying gas H2 is 25-35 sccm, and the flow rate of Ar is 350-450 sccm.
6. The method for preparing carbon nanocomposite fibers according to claim 1, wherein: The concentration of the OMC solution is 0.1-1 mg / ml.
7. The carbon nanocomposite fiber obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The carbon nanocomposite fiber uses multi-walled carbon nanotubes as a skeleton and is highly arranged along the axial direction, and the ordered porous carbon is interconnected between the aligned multi-walled carbon nanotubes.
8. Use of the carbon nanocomposite fiber as claimed in claim 7 in preparing a flexible weavable capacitor.
9. A flexible woven capacitor, characterized in that: The carbon nanocomposite fiber according to claim 7 is used as an electrode.
10. The method for preparing a flexible weavable capacitor according to claim 9, characterized in that: include, Polyvinyl alcohol is added to deionized water, stirred at room temperature for 5 to 7 hours, and then heated at 80 to 100° C. under magnetic stirring conditions to obtain a mixed solution, and H3PO4 is added to the mixed solution to generate a gel electrolyte, wherein the mass ratio of the polyvinyl alcohol to H3PO4 is 1:1 to 2, and the mass volume ratio of the polyvinyl alcohol to the deionized water is 1 g:8 to 12 ml; The surfaces of every two carbon nanocomposite fiber MWCNT / OMC composite materials are coated with gel electrolyte and twisted together to form a filamentary electric double layer capacitor EDLC, which is a flexible weavable capacitor based on carbon nanocomposite fibers.